Backbone and ILV methyl resonance assignments of E. coli thymidylate synthase bound to cofactor and a nucleotide analogue - Sapienza, Paul J. (2013)
Thymidylate synthase (TSase) is a 62 kDa homodimeric enzyme required for de novo synthesis of thymidine monophosphate (dTMP) in most organisms. This makes the enzyme an excellent target for anticancer and microbial antibiotic drugs. In addition, TSase has been shown to exhibit negative cooperativity and half-the-sites reactivity. For these collective reasons, TSase is widely studied, and much is known about its kinetics and structure as it progresses through a multi-step catalytic cycle. Recently, nuclear magnetic resonance (NMR) spin relaxation has been instrumental in demonstrating the critical role of dynamics in enzyme function in small model systems. These studies raise questions about how dynamics affect function in larger enzymes with more complex reaction coordinates. TSase is an ideal candidate given its size, oligomeric state, cooperativity, and status as a drug target. Here, as a pre-requisite to spin relaxation studies, we present the backbone and ILV methyl resonance assignments of TSase from Escherichia coli bound to a substrate analogue and cofactor.